An introduction to Feng shui - Bruun, Ole (Cambridge University Press, 2008)
List of illustrations -- 1: Introduction -- Feng shui as popular religion -- Three themes -- Western receptiveness -- 2: Brief History Of Feng Shui -- Classical age -- Imperial age -- Colonial era -- Communist era -- 3: Feng Shui In The Context Of Chinese Popular Religion -- Family ritual and the yearly festivals -- Chinese almanac, or the know all book (Tongshu) -- Feng shui for building -- Feng shui for burial -- Other common applications -- Feng shui and belief -- Feng shui and other strands of popular divination -- 4: Feng Shui Research -- New turn -- Studies in ecology and nature perception -- Studies in architecture -- 5: Cosmological Principles, Schools Of Interpretation And The Feng Shui Compass -- Book of changes -- Five elements (wu xing) -- Concept of qu (ch'i) -- Schools of feng shui -- Feng shui compass -- 6: Feng Shui In The Chinese Cityscape: China Proper And Overseas -- Cities in China proper -- Taiwan and Hong Kong -- 7: Modern Feng Shui Interpretations And Uses -- New perspective on an old subject -- New schools of feng shui -- Renewed exposure in China -- New feng shui uses: western, Chinese or global? -- Manual authors -- Global exchange -- Corporate feng shui? -- 8: Environmental Concerns -- History and environment in China -- Some fieldwork experiences -- New Chinese environmentalism -- 9: Feng Shui As Cultural Globalization? -- Bibliography -- Index